2022
DOI: 10.1002/cncr.34478
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib dose optimization based on therapeutic drug monitoring in Chinese patients with chronic‐phase chronic myeloid leukemia

Abstract: Background: Imatinib treatment often produces various adverse reactions in patients with chronic myeloid leukemia (CML), and increasing patients are pursuing dose optimization. In this study, the authors aimed to explore imatinib dose optimization based on therapeutic drug monitoring (TDM) in CML patients. Methods:The relationship between imatinib concentration and clinical response and adverse reactions was evaluated, then the dose-reduction data in 110 Chinese CML patients was also explored.Results: Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The authors have no conflicts of interest to declare. Fang Cheng MD 1,2 Fang Zeng MD 1,2 Qiang Li PhD 1,2 Zheng Cui PhD 1,2 Yilin Chen MD 3 Weiming Li PhD 3 Yu Zhang PhD 1,2 1…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The authors have no conflicts of interest to declare. Fang Cheng MD 1,2 Fang Zeng MD 1,2 Qiang Li PhD 1,2 Zheng Cui PhD 1,2 Yilin Chen MD 3 Weiming Li PhD 3 Yu Zhang PhD 1,2 1…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…1 In patients with CML-CP, it was previously shown that imatinib concentrations could be associated with clinical responses. 2,3 Cheng et al 4 have demonstrated that, in addition to therapeutic efficacy, plasma imatinib trough levels are also associated with toxicities.…”
Section: Dear Editormentioning
confidence: 99%
“…1 In patients with CML-CP, it was previously shown that imatinib concentrations could be associated with clinical responses. 2,3 Cheng et al 4 have demonstrated that, in addition to therapeutic efficacy, plasma imatinib trough levels are also associated with toxicities.Although this is a very informative study with very interesting findings, there are still some points that need to be further underlined:� The authors stated that they included patients with "good compliance"; however, they did not define what was accepted as good compliance. Previously, Marin and colleagues 5 clearly showed that patients with an imatinib adherence rate of >90% had significantly higher rates of major molecular response (MMR) and deep molecular response than those with an adherence rate of…”
mentioning
confidence: 99%
See 2 more Smart Citations